2008
DOI: 10.1089/acm.2006.6408
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Canines in the Detection of Human Cancers

Abstract: Although this study did not produce the outcomes desired, the literature supports a potential to use canines for human cancer detection. Better management of urine samples and a more stringent training protocol during our study may have provided new evidence as to the feasibility of using canines for cancer detection. A comparison of the 3 dog cancer scenting studies is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 22 publications
6
99
0
1
Order By: Relevance
“…However, under controlled circumstances they may be used in experiments to further explore this very interesting new property of malignancies. Similar suggestions were recently published by Gordon et al 6 …”
Section: Discussionsupporting
confidence: 91%
“…However, under controlled circumstances they may be used in experiments to further explore this very interesting new property of malignancies. Similar suggestions were recently published by Gordon et al 6 …”
Section: Discussionsupporting
confidence: 91%
“…The outstanding sensitivity of the canine olfactory system has been acknowledged by using sniffer dogs in military and civilian Inter-ratervariability k 0.436 service for detection of a variety of odours. Moreover, sniffer dogs have been employed in pre-clinical studies for cancer diagnosis [22,23]. In 2006, MCCULLOCH et al [14] reported a sensitivity and specificity of 99% for sniffer dogs to diagnose lung cancer from patients' breath samples.…”
Section: Discussionmentioning
confidence: 99%
“…Breath seems to serve as a better sample for canine discrimination than urine that was also proposed as a potentially good source of endogenously produced volatile compounds. In a recent study, GORDON et al [42] could not train their dogs for proper discrimination of urine samples between patients with breast or prostate cancer from that of controls. According to a hypothesis, VOCs produced by tumours and detected by dogs are the products of major histocompatibility complex (MHC) genes [43].…”
Section: Canine Smellmentioning
confidence: 99%